Ruby fever - Andrews, Ilona (Andrews, Ilona. Hidden legacy series, 2022)
"An escaped spider, the unexpected arrival of an Imperial Russian Prince, the senseless assassination of a powerful figure, a shocking attack on the supposedly invincible Warden of Texas, Catalina's boss... And it's only Monday. Within hours, the fate of Houston-not to mention the House of Baylor-now rests on Catalina, who will have to harness her powers as never before. But even with her fellow Prime and fiancé Alessandro Sagredo by her side, she may not be able to expose who's responsible before all hell really breaks loose."--